2011
DOI: 10.1016/j.socscimed.2011.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Infertility treatment and fertility-specific distress: A longitudinal analysis of a population-based sample of U.S. women

Abstract: Because research on infertile women usually uses clinic-based samples of treatment seekers, it is difficult to sort out to what extent distress is the result of the condition of infertility itself and to what extent it is a consequence of the experience of infertility treatment. We use the National Survey of Fertility Barriers, a two-wave national probability sample of U.S. women, to disentangle the effects of infertility and infertility treatment on fertility-specific distress. Using a series of ANOVAs, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 60 publications
(97 reference statements)
6
99
0
7
Order By: Relevance
“…Furthermore, neither items measuring fertilityspecific distress [18,20] nor information about whether the respondent was actively trying to get pregnant, whether she self-identified as infertile, had undergone ART treatment or had adopted a child was included. Finally, levels of anxiety and depressive symptoms were assessed by means of a selfreport instrument.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, neither items measuring fertilityspecific distress [18,20] nor information about whether the respondent was actively trying to get pregnant, whether she self-identified as infertile, had undergone ART treatment or had adopted a child was included. Finally, levels of anxiety and depressive symptoms were assessed by means of a selfreport instrument.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, the association between infertility and symptoms of common mental conditions may be less pronounced in the general female population than in infertility clinic attendees [14], as the less than half of couples [15,16] with infertility who seek medical help are more likely to have a longer duration of infertility, higher levels of distress and higher prevalence of co-morbid somatic conditions than non-help-seeking couples [7,17]. In addition, fertility treatment is associated with levels of distress over and above those associated with the state of being infertile in and of itself [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example it has been revealed that during natural disasters like earthquakes, sperm quality activities of seminal plasma superoxide dismutase and arginine decrease, and nitric oxide levels increase in men under stress (7,8). Since psychiatric disorders are more frequently analyzed during infertility investigations, scales specific to infertility process haven't been developed yet (9). In developed countries, it appears to be appropriate to take a detailed history about psychological status of the infertile couple.…”
mentioning
confidence: 99%
“…The proportion of women in the US who experience infertility using the ASRM definition is 7% to 15.5% in a given year depending upon specific measurement procedures (Thoma et al 2013). The percentage is substantially higher (51.8%) for women who have met the ASRM criteria at some point throughout their reproductive lifespan (Greil et al 2011a). Little is known about how women who experience infertility (e.g., meet the medical criteria) or identify as having a fertility problem (i.e., with or without meeting the medical criteria) think about their fertility intentions and desires compared to women without infertility experiences.…”
Section: Introductionmentioning
confidence: 99%